Effect of lignin and plant growth-promoting bacteria (Staphylococcus pasteuri) on microbe-plant Co-remediation: A PAHs-DDTs Co-contaminated agricultural greenhouse study. (October 2020) - Zheng, Xuehao; Aborisade, Moses Akintayo; Wang, Hui; He, Peng; Lu, Shan; Cui, Na; Wang, Songyuan; Zhang, Hongling; Ding, Hui; Liu, Kebin
Abstract: Due to the ecological toxicity and environmental residues, how to remove the persistent organic pollutants (POPs), especially of polycyclic-aromatic-hydrocarbons (PAHs) and dichloro-diphenyl-trichloroethanes (DDTs), from agricultural soil has captured the attention of scholars for a long time. To develop an effective and low-cost in situ co-remediation technique, five independent but complementary treatments were used on an over-standard PAHs-DDTs co-contaminated soil in an agricultural greenhouse. Experimental results identified that the combination of microbe ( Bacillus methylotrophicus ) - plant ( Brassica rapa ) could remove rhamnolipid activated PAHs and DDTs effectively after enhanced by Staphylococcus pasteuri . Also, the Benzoapyrene and total DDTs residue in Brassica rapa was up to the standard of National (China) food safety. The lignin enhanced the removal of high-rings PAHs and p-p' DDE but reduced soil microbial biomass carbon and soil enzymes activity (polyphenol oxidase, invertase and acid phosphatase). Pearson correlation analysis showed that polyphenol oxidase activity was significantly related to the PAHs/DDTs dissipation rate. Our research suggested a new amendment that could remediate PAHs/DDTs co-contaminated agricultural soil without interrupting crop production, and the polyphenol oxidase activity should be considered as a micro-ecological indicator in this process. Graphical abstract: Image 1 Highlights: Remediate PAHs/DDTs contaminated soil without interrupting agricultural production. Lignin enhanced the removal of high-rings PAHs and p-p' DDE. Staphylococcus pasteuri protect plants from organic pollutants accumulation. Polyphenol oxidase was a micro-ecological indicator during the remediation.